FAKTOR PENENTU PERBEDAAN KEAKTIFAN BELAJAR GEOGRAFI PADA SISWA KELAS E1 DAN E5 DI SMAN 11 PADANG - Zalfani Putri; Afdhal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the determinants of differences in geography learning activity in grades E1 and E5 at SMAN 11 Padang. The research method used is comparative qualitative. Informants in this study consisted of 10 people, namely 9 students and 1 geography teacher. Data were collected using interviews, observation, and documentation. The data validity test used was the triangulation technique, then analysis used data reduction, data presentation, and conclusion drawing. The results of the study showed that: 1) E1 was more active in discussions and questions and answers, while E5 tended to be passive except when learning outside the classroom or using interactive media. 2) There was a significant difference, E1 was more active and confident in conventional methods, while E5 was hampered by shame and fear of making mistakes. 3) Differences in activity were determined by internal factors (understanding of the material, self-confidence, physical condition) and external factors (teacher strategies, teacher responses, social environmental support, and facilities).